Modern tendencies in osteosynthesis of metaphyseal and metadiaphyseal fractures of long bones (a review of literature) - Tyazhelov, Olexiy; Poletaeva, Nataliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The literature review highlights the problem of finding the optimal treatment of unstable and metadiafizarnyh metaphyseal fractures of long bones. The advantages and disadvantages of outdoor, intramedullary, osteosynthesis of these fractures, the specificity with respect to the indications for each of these methods.